Evaluating the directional stability of alpine skis through the simulation of ski deformation during a steady-state turn - Truong, J.; Lussier Desbiens, A. (Proceedings, 2018)
Directional stability is an important performance criterion for alpine skis and has been shown to correlate with the second moment of running surface pressure distribution. However, this stability index is complex to measure while skiing and is not practical for testing many skis. It therefore remains unclear what range one can expect in the variation of stability between commercially available skis. In this study, the mechanical properties of 179 skis were measured and the ski deformation was simulated during a steady-state turn to evaluate the stability index. The resulting data provide insight as to what values of stability, which ranged from 0.1 to 98 N m², are to be expected. A novel parameter, the product of the force required to flatten a ski and the square of its sidecut length, was introduced. Its high correlation with a ski`s stability suggests it can be used as an accurate predictor of stability.